Teratogenic Tinospora Cordifolia And Carica Papaya On White Mouse Fetuses (Mus Musculus) - ardiyantoro, Bagas; arniwati mat daud, Noor (LPPM Universitas Duta Bangsa Surakarta, 2024)
Tinospora cordifolia and Carica papaya in the production of traditional herbal medicines, specifically in formulations known as tinospora cordifolia and Carica papaya herbal mixtures. Extracts from Tinospora cordifolia stems and Carica papaya contain bioactive flavonoid antioxidants, which can inhibit phosphodiesterase enzymes that hydrolyze cAMP. Elevated cAMP concentrations can impede growth acceleration. This research aims to assess the teratogenic effects on the fetuses of white mice after administering tinospora cordifolia and carica papaya extracts. The study involved 25 Mus musculus divided into five groups. The first group, serving as the negative control, received 0.5% Na CMC, while the second group, serving as the positive control, was injected with intravenous Cyclophosphamide at 50 mg/kg. The other groups were administered various doses: ET Dose 1120, ECP Dose 1120, Dose 1 ETCP 2:1, Dose 2 ETCP 1:2, and Dose 3 ETCP 1:1. The extracts were given during the organogenesis period, and on the 18th day, the mice underwent laparotomy to collect the fetuses. The research findings indicate that tinospora cordifolia and carica papaya extracts can cause teratogenic effects, particularly at Dose 3 ETCP 1:1.